Association of HLA-DQB1*0501 with Scleroderma and its Clinical Features in Chinese Population. (July 2013) - Zhou, X.D.; Yi, L.; Guo, X.J.; Chen, E.; Zou, H.J.; Jin, L.; Mayes, M.D.; Assassi, S.; Wang, J.C.
Specific human leukocyte antigen (HLA) DQB1 alleles confer strong susceptibility to systemic sclerosis (SSc). However, the frequencies of specific DQB1 alleles and their associations with SSc vary according to ethnicity and clinical features of SSc. The aim of this study was to profile DQB1 alleles in a Chinese population and to identify specific DQB1 alleles in association with SSc of Han Chinese. A cohort containing 213 patients with SSc and 239 gender-matched and unrelated controls was examined in the study. The HLA-DQB1 genotyping was performed with sequence-based typing (SBT) method. Exact p-values were obtained (Fisher's test) from 2×2 tables of allele counts or allele carriers and disease status. Seventeen DQB1 alleles were found in the cohort. DQB1*03:03 was the most common allele in this cohort. DQB1*05:01 was significantly increased in SSc, and was strongly associated with anticentromere autoantibodies (ACA). Compared with SSc in other ethnic populations, SSc patients of Han Chinese are distinct in association with DQB1*06:11, common in association with DQB1*05:01, but lack association with DQB1*03:01. In addition, DQB1*06:01 appeared more common in ATA-positive Chinese SSc, and marginally associated with pulmonary fibrosis, and an increased frequency of DQB1*03:03 was observed in anti-U1RNP-positive Chinese SSc patients.